Faktor penentu pelaporan maklumat penyelidikan dan pembangunan (R&D) di Malaysia - Hashim, Fathyah; Jaffar, Romlah (Universiti Utara Malaysia, 2006)
Information on the research and development activities (R&D) is among the most important information sought by investors especially of companies involved in technology-based industry. This paper examines the disclosure of R&D information in the annual reports of companies listed in the Main Board of the Kuala Lumpur Stock Exchange (KLSE) for the year 2002. Specifically,the research seeks to investigate the level of R&D information disclosure and the factors that may affect the level of this disclosure. Eighty-seven out of 314 companies from techbology, consumer goods, industrial products, and trading and services industries were chosen as samples of this study. Analysis of variance (ANOVA) was used to analyse the data. The results of the study show that company size and capital structure variables are significant in explaining the level of R&D disclosure. In contrast, international operation and type of industry are not significant explanatory variables. The results of the study provide an implication that companies need to give serious consideration in reporting this information since investors need this information to make investing decisions.